2011
DOI: 10.1016/j.coviro.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of neuraminidase inhibitor-resistant influenza A viruses

Abstract: Antiviral drugs are important components for the control of influenza. The key question is whether antiviral use or natural virus evolution will lead to the emergence of drug-resistant virus with comparable or superior fitness to drug-susceptible counterpart. Currently, neuraminidase (NA) inhibitors (NAIs) are the first choice for influenza prevention and treatment. In this article we will review complex process of the risk assessment for the fitness of NAIs-resistant seasonal H1N1 and H3N2, pandemic 2009 H1N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…For example, the V234M and R222Q mutations help to decrease NA folding and transport defects by increasing the amount of NA reaching the cell surface and thus compensate for the active site mutation H274Y (Baranovich et al, 2011). These findings highlight the possibility of mutations on residues other than catalytic or framework residues causing resistance to NAIs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, the V234M and R222Q mutations help to decrease NA folding and transport defects by increasing the amount of NA reaching the cell surface and thus compensate for the active site mutation H274Y (Baranovich et al, 2011). These findings highlight the possibility of mutations on residues other than catalytic or framework residues causing resistance to NAIs.…”
Section: Discussionmentioning
confidence: 94%
“…Although most resistant mutants arise in response to NAI treatments, several other reports have also documented naturally occurring antigenic drift mutations that alter the susceptibility of H5N1 viruses to NAIs in the absence of any drug selection pressure (Baranovich et al, 2011;RameixWelti et al, 2006;Stoner et al, 2010). The contamination of OTV in the environment (water or sewage) has been reported in Japan (Ghosh et al, 2010;Söderström et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported that NA mutations associated with resistance to NA inhibitors compromise viral fitness in vitro and in vivo (Baranovich et al, 2011). We also observed that a recombinant HPAI H7N9 virus with R294K, generated on the basis of the consensus sequence of the GD/3 virus stock, was attenuated in differentiated NHBE cells, mice, and ferrets relative to its NA inhibitor-sensitive counterpart, suggesting that the reduction in replicative fitness of HPAI H7N9 viruses is caused by the R294K mutation.…”
Section: Discussionmentioning
confidence: 99%
“…For future drug design and resistance expectation, it is important to learn that the effect of these mutations is dependent both on the NA subtype and the drug used [55,56]. Generally, catalytic site mutants exhibit drug resistance, but also show decreased NA activity, such that viral infectivity, pathogenicity and transmissibility are affected.…”
Section: Reviewmentioning
confidence: 99%